2013
DOI: 10.1103/physrevb.87.214522
|View full text |Cite
|
Sign up to set email alerts
|

Elastic constants of incommensurate solid4He from diffusion Monte Carlo simulations

Abstract: We study the elastic properties of incommensurate solid 4 He in the limit of zero temperature. Specifically, we calculate the pressure dependence of the five elastic constants (C 11 , C 12 , C 13 , C 33 , and C 44 ), longitudinal and transversal speeds of sound, and the T = 0 Debye temperature of incommensurate and commensurate hcp 4 He using the diffusion Monte Carlo method. Our results show that under compression, the commensurate crystal is globally stiffer than the incommensurate, however at pressures clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…For instance, the elastic properties of the incommensurate crystal in the limit of zero temperature have been analysed by Cazorla, Lutsyshyn, and Boronat (2013); it has been shown that when considering large vacancy concentrations (x v ∼ 1 %) the shear modulus of the solid undergoes a small reduction of just few percent with respect to the perfect crystal case.…”
Section: A Vacanciesmentioning
confidence: 99%
“…For instance, the elastic properties of the incommensurate crystal in the limit of zero temperature have been analysed by Cazorla, Lutsyshyn, and Boronat (2013); it has been shown that when considering large vacancy concentrations (x v ∼ 1 %) the shear modulus of the solid undergoes a small reduction of just few percent with respect to the perfect crystal case.…”
Section: A Vacanciesmentioning
confidence: 99%
“…Specifically, the lattice vectors describing our simulation cell are a 1 = (L x , 0, 0), a 2 = (x 2 , L y , 0), and a 3 = (x 3 , y 3 , L z ), where x 3 represents the introduced tilt. The corresponding shear strain is η xz = x 3 /L z , and the resulting shear stress can be estimated as [35][36][37]:…”
Section: Methods B: Periodic Boundary Conditionsmentioning
confidence: 99%
“…2,34 The computational strategy that we followed to calculate the shear modulus C 44 was the same than in Refs. [35][36][37].…”
Section: B Diffusion Monte Carlomentioning
confidence: 99%
“…In order to quantify the importance of quantum nuclear effects on the calculation of the shear modulus, we carried out additional quantum DMC calculations (see Sec. II B and works [35][36][37] for details). To our surprise, we found that the quantum and classical shear modulii results are very similar.…”
Section: Elastic Propertiesmentioning
confidence: 99%